Rethinking Concepts of De-Radicalization: an Effort to Mitigate Radicalism Through Education - Handajani, Aniek (IJBLE Scientific Publications Community Inc., 2024)
A rise in radicalism and violence in Indonesia leads to important questions of how individuals be ‘radicalized’ that makes it difficult to combat radicalism. Hence, attempt to mitigate radicalism requires understanding the radicalization process and the concept of de-radicalization. This study aims at stimulating discussion on theories of radicalization and rethinking concepts of de-radicalization. This research addresses the question on how theories of radicalization process relate to efforts of de-radicalization through education applied recently in Indonesia. This study is a qualitative approach with a descriptive type of library research which uses theories of radicalization and concepts of de-radicalization as research data. This research critically analyses theories of de-radicalization on an attempt to mitigate radicalism through education. There are many models explaining the radicalization process toward an individual. Among the existing models of radicalization process, two influential models are Wiktorowicz’s model and Sinai’s model. Furthermore, based on researches of de-radicalization, concepts of Pressman and Golose give a comprehensive concept of de-radicalization and support efforts to mitigate radicalism through education. This study also proposes some strategies to mitigate radicalism in schools